Hospitalization due to drug use did not change after a decade of the Psychiatric Reform - Alexandre Dido Balbinot; Rogério Lessa Horta; Juvenal Soares Dias da Costa; Renata Brasil Araújo; Simone Poletto; Marina Bressaneli Teixeira (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To investigate whether the psychiatric hospitalization rates due to use of psychoactive substances and average time of hospitalization suffered any changes after the first decade of effective implementation of the psychiatric reform in Brazil. METHODS This article examines the evolution of hospitalizations due to disorders arising from the use of alcohol or other substances in the state of Santa Catarina, Southern Brazil, from 2000 to 2012. This is an ecological, time-series study, which uses data from admissions obtained by the Informatics Service of the Brazilian Unified Health System. Hospitalization rates by 100,000 inhabitants and average time of occupancy of beds were estimated. Coefficients of variation of these rates were estimated by Poisson Regression. RESULTS The total and male hospitalization rates did not vary (p = 0.056 and p = 0.244, respectively). We observed an increase of 3.0% for the female sex (p = 0.049). We did not observe any significant variation for occupancy time of beds. CONCLUSIONS The deployment of services triggered by the Brazilian psychiatric reform was not accompanied by a reduction of hospitalization rates or mean occupancy time of hospitalized patients during this first decade of implementation of the reform.